2017
DOI: 10.1038/srep46056
|View full text |Cite
|
Sign up to set email alerts
|

Oxoaporphine Metal Complexes (CoII, NiII, ZnII) with High Antitumor Activity by Inducing Mitochondria-Mediated Apoptosis and S-phase Arrest in HepG2

Abstract: Three new oxoaporphine Co(II), Ni(II) and Zn(II) complexes 1–3 have been synthesized and fully characterized. 1–3 have similar mononuclear structures with the metal and ligand ratio of 1:2. 1–3 exhibited higher cytotoxicity than the OD ligand and cisplatin against HepG2, T-24, BEL-7404, MGC80–3 and SK-OV-3/DDP cells, with IC50 value of 0.23−4.31 μM. Interestingly, 0.5 μM 1–3 significantly caused HepG2 arrest at S-phase, which was associated with the up-regulation of p53, p21, p27, Chk1 and Chk2 proteins, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 70 publications
(87 reference statements)
4
27
0
Order By: Relevance
“…The present study observed that dark-colored maple syrup treatment decreased PCNA expression, which induced the S-phase cell cycle arrest of DLD-1 cells. Previous reports also indicate that induction of S-phase cell cycle arrest is accompanied by decreased PCNA expression in a number of tumor cells, including in CRC cells treated with functional compounds, such as resveratrol and oxoaporphine metal complexes (51,52). Previous data also indicate that the induction of S-phase cell cycle arrest is associated with changes in the expression of cyclins and CDKs in these cells.…”
Section: Discussionmentioning
confidence: 94%
“…The present study observed that dark-colored maple syrup treatment decreased PCNA expression, which induced the S-phase cell cycle arrest of DLD-1 cells. Previous reports also indicate that induction of S-phase cell cycle arrest is accompanied by decreased PCNA expression in a number of tumor cells, including in CRC cells treated with functional compounds, such as resveratrol and oxoaporphine metal complexes (51,52). Previous data also indicate that the induction of S-phase cell cycle arrest is associated with changes in the expression of cyclins and CDKs in these cells.…”
Section: Discussionmentioning
confidence: 94%
“…The stimulation of p53, as one of the key regulators of cell cycle, can induce apoptosis. However, the concurrent Bcl-2 and survivin stimulation suggests at a functional protective mechanisms in the cells [41]. On the other hand, homing via GASNGINAYLC peptide led to up-regulation of p53 together with downregulation of both Bcl-2 and survivin.…”
Section: Discussionmentioning
confidence: 96%
“…[33][34][35] Electric current causes the fragment of lamellar cementite to be perpendicular to current. [26] Since there is a gap between the new cementite plates, the current flows through the gap, leading in the improvement of conductivity, [20,26] as shown in Figure 12c.…”
Section: Interaction Of Inclusionsmentioning
confidence: 99%
“…[24] The numerical calculation shows that the elliptical disk particle with a lower conductivity than liquid tends to rotate in the direction of the electric current, [25] whereas the particle perpendicular to the current direction tends to break into smaller ones. [26] In fact, aggregation and collision of nonmetallic inclusions inevitably occur in the molten metal. However, the model built by Qin or Kolin is based on one single particle.…”
Section: Introductionmentioning
confidence: 99%